Impact of psychosocial training on burnout, engagement and resilience among students - Zuzana Škodová; Petra Lajčiaková (University of Ostrava, 2015)
Aim: The objective of the study was to investigate the effect of psychosocial training, with a focus on increasing social and coping skills, on the levels of burnout and engagement in students in various healthcare professions. Design: A quasi-experimental design was used in the present study. Methods: 97 students (20.2 ' 1.49; 95.9% female) of psychology, nursing and midwifery participated in the research (50 students in an experimental group receiving psychosocial training, and 47 students in a control group). To measure burnout, the School Burnout Inventory (SBI), Antonovski Sense of Coherence Scale (SOC), Utrecht Work Engagement Scale (UWES) and Baruth Protective Factors Inventory (BPFI) were employed. Data were statistically analyzed using correlation analysis, Student's t-test, and the ANOVA with LSD post hoc tests. Results: A statistically significant decrease in burnout syndrome (95 % CI: 5.26; 11.94), and an increased sense of coherence (95 % CI: -11.48; -3.37) and resilience (95 % CI: -7.92; -1.70) were found in the experimental group of students after psychosocial training, while no significant changes were observed in the control group. Research assumptions regarding engagement were not confirmed. Conclusion: The research study has shown that psychosocial training as a method has a positive effect on burnout syndrome and related personality characteristics among students of the healthcare professions, and is thus a relevant and appropriate method of burnout prevention.